Transcriptome Analysis in Haematococcus pluvialis: Astaxanthin Induction by High Light with Acetate and Fe(2+) - He, Bangxiang (Int J Mol Sci, 2018)
Haematococcus pluvialis is a commercial microalga, that produces abundant levels of astaxanthin under stress conditions. Acetate and Fe(2+) are reported to be important for astaxanthin accumulation in H. pluvialis. In order to study the synergistic effects of high light stress and these two factors, we obtained transcriptomes for four groups: high light irradiation (HL), addition of 25 mM acetate under high light (HA), addition of 20 μM Fe(2+) under high light (HF) and normal green growing cells (HG). Among the total clean reads of the four groups, 156,992 unigenes were found, of which 48.88% were annotated in at least one database (Nr, Nt, Pfam, KOG/COG, SwissProt, KEGG, GO). The statistics for DEGs (differentially expressed genes) showed that there were more than 10 thousand DEGs caused by high light and 1800–1900 DEGs caused by acetate or Fe(2+). The results of DEG analysis by GO and KEGG enrichments showed that, under the high light condition, the expression of genes related to many pathways had changed, such as the pathway for carotenoid biosynthesis, fatty acid elongation, photosynthesis-antenna proteins, carbon fixation in photosynthetic organisms and so on. Addition of acetate under high light significantly promoted the expression of key genes related to the pathways for carotenoid biosynthesis and fatty acid elongation. Furthermore, acetate could obviously inhibit the expression of genes related to the pathway for photosynthesis-antenna proteins. For addition of Fe(2+), the genes related to photosynthesis-antenna proteins were promoted significantly and there was no obvious change in the gene expressions related to carotenoid and fatty acid synthesis.